Orobanche javakhetica (Orobanchaceae): a new species from the Caucasus (Armenia) - Piwowarczyk, Renata; Sánchez Pedraja, Óscar; Moreno Moral, Gonzalo; Denysenko-Bennett, Magdalena; Góralski, Grzegorz; Kwolek, Dagmara (Phytotaxa, 2018)
Orobanche javakhetica (Orobanchaceae) is described as a new, probably endemic, species from the Lesser Caucasus in Armenia. It grows on a subalpine meadow, where it parasitises Lomelosia caucasica (Dipsacaceae). The newly-described species is very characteristic and different from other known Orobanche, however some morphological similarity may exist with species from the Orobanche subsect. Curvatae, particularly with species of the Orobanche series Krylowianae. A detailed description, illustrations, a comparison with the most similar species with identification key, and phylogenetic analysis are provided.